The Influence of Transformational Leadership Style, Work Discipline, and Compensation on the Performance of the State Civil Apparatus Through Motivation - Hasanudin, Hasanudin; Nugroho, Romualdus Adi (Almana : Jurnal Manajemen dan Bisnis, 2023)
An organization expects its resources to solve its problems. The main problem faced by an organization is the productivity of its human resources. This study aims to determine and analyze the influence of transformational leadership style, work discipline, and compensation on employee performance through motivation. This research is statistical quantitative research obtained from data collection in research sourced from primary data and secondary data. The population in this study was employees of the Secretariat General of the DPR RI who worked in the Building and Guest House Bureau section, and the number of samples used was 133 people. Data collection was carried out by distributing questionnaires and the analysis technique used was SEM-PLS. The results showed that transformational leadership style, work discipline, compensation, and motivation directly affect employee performance. Motivation mediates the influence of transformational leadership style, work discipline, and compensation on employee performance.